2009
DOI: 10.1103/physrevlett.102.146404
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Statistics and Quantum Scaling Properties of the Hubbard Chain with Bond-Charge Interaction

Abstract: We present a detailed study of the ground state and low-temperature properties of the integrable Hubbard model with bond-charge interaction, including its conducting properties and scaling behavior near the U-driven quantum phase transitions. Remarkably, the model displays fractional statistical properties, which enlighten the nature of various physical properties, such as the fractional elementary excitations, and give rise to a disordered condensate and phase separation in k space, as well as to a topologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
(45 reference statements)
0
23
0
Order By: Relevance
“…In Ref. 26, the authors have pointed out that the thermodynamic properties of the model in Eq. ͑2͒ is that of an ideal excluson gas with three fractional species, ͗n k,␣ ͘,…”
Section: Model and Exclusion Representationmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ref. 26, the authors have pointed out that the thermodynamic properties of the model in Eq. ͑2͒ is that of an ideal excluson gas with three fractional species, ͗n k,␣ ͘,…”
Section: Model and Exclusion Representationmentioning
confidence: 99%
“…14 Further, other Hamiltonian models obeying fractional exclusion statistics have been studied, such as: multicomponent Sutherland model, 15 quantum Calogero model, 16 model describing onedimensional relativistic fermions interacting with the Toda array of N scalar fields, 17 Hubbard model with infinite-range interaction, 18 exclusion statistics and signature of strongly interacting anyons, 19 strongly interacting one-dimensional Bose gas, 20 gas of neutral fermionic atoms at ultralow temperatures with the attractive interaction tuned to Feshbach resonance, 21 phase transitions and pairing signature in strongly attractive Fermi atomic gases, 22 entanglement entropy in the Calogero-Sutherland model, 23 statistical correlations in an ideal gas of particles, 24 and many-spinon states and representations of Yangians in the SU͑n͒ HaldaneShastry model. 25 Recently, the authors 26 have shown that the exactly solvable Hubbard chain with bond-charge interaction is mapped onto an ideal gas of three species of exclusons. Remarkably, the statistical matrix for this model with on-site interaction is the same found for the Hubbard model with infinite-range interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, such terms were reconsidered as an alternative scheme for high-T c superconductivity [28,29]. For particular parameter values the Hamiltonian for a Hubbard chain turns out to be integrable [30] and displays fractional statistics [31]. The occupation-number sensitivity of tunnelling was even implemented experimentally by employing the high-resolution quantum gas microscope technique [32].…”
Section: Introductionmentioning
confidence: 99%
“…The present work is intended to fill this gap, by investigating the behavior of QD and CC for the ground states of the one-dimensional bond-charge extended Hubbard model 32,33 , which is a reference model in correlated-electron theory. The model has an integrable point, and its entanglement properties have been the subject of recent studies [34][35][36][37][38] where use of two-point and multipartite entanglement measures led to a classification of QPTs into multipartite or two-point driven. These studies left open the problem of addressing the general role of bipartite correlations for all twopoints driven QPTs, as well as their relation with the presence of off diagonal long range order (ODLRO) which characterizes some ordered phases of the model.…”
Section: Introductionmentioning
confidence: 99%